(untitled) (Research, Society and Development, 2025)
Introduction: HSG is considered the gold standard for assessing tubal patency, consisting of the injection of radiopaque contrast followed by radiographic analysis. Despite its effectiveness, the method has limitations such as discomfort, risk of adverse reactions, and exposure to ionizing radiation. HyCoSy, in turn, uses transvaginal ultrasonography associated with echogenic contrast agents, allowing real-time evaluation without radiation exposure and with greater patient comfort, with both methods presenting distinct characteristics and indications. Methodology: This study aims to perform, through a narrative literature review, a comparison between hysterosalpingography and hiscosalpingography examinations, considering aspects of diagnostic accuracy, safety, comfort, costs, and therapeutic potential. Discussion: The analysis of the studies shows that HyCoSy demonstrates diagnostic sensitivity and accuracy comparable to HSG, with advantages such as lower morbidity, absence of radiation, and the ability to evaluate the uterus and fallopian tubes simultaneously. However, technical limitations, the need for greater expertise, and the cost of specific contrast agents still restrict its large-scale use. The literature indicates that HSG remains central as an initial exam, while HyCoSy stands out as a promising and complementary alternative. Conclusion: The findings show that HyCoSy offers accuracy comparable to HSG, with greater sensitivity, comfort, and safety. However, technical limitations and costs restrict its widespread implementation. The choice of method should be individualized, considering available resources, clinical profile, and patient well-being.